A BRIEF CONCEPT OF CHATUSKA IN BRIHATRAYEE - Khagen Basumatary; Chumi Bhatta* (AYUSHDHARA, 2019)
Ayurveda, the science of life is the ancient Indian medicine which deals with longevity of life. The main purpose of Ayurveda is to maintain the health of the healthy individual and treatment of the diseased Individual. This entire concept is mainly described in Samhita. There are three fundamental authoritative texts in Ayurveda called Brihatrayee -Charak samhita, Susruta samhita, Astanga hridaya. Charak samhita contains 8 Sthanas, Susruta samhita contains 5 Sthanas and Astanga hridaya contains 5 sthanas. Among them Sutrasthana is the most important and it is collective form of whole Samhita. The Sutrasthan of Charak samhita mentioned “Triskanda” in which entire Samhita is based. Again Sutrasthana of Susruta samhita mentioned about “Bijachatustaya” which is similar to Triskanda and the whole Susruta samhita is based. In Charak samhita the Sutra sthana is divided in seven Chatuska. This is the solitary characteristics of Charak samhita. We do not find such type of classification in other Samhita. Hence a humble effort has been made to rearrange the Sutrasthan of Susruta samhita and Astanga hridaya in the form of Chatuska and to give probable explanation for their arrangement.